Energy efficiency control of pneumatic actuator systems through nonlinear dynamic optimization. (20th May 2018) - Du, Hongwang; Xiong, Wei; Jiang, Zhong'ai; Li, Qiu; Wang, Lu
Abstract: As one of the most widely used power sources in the engineering field, compressed air is especially common in industrial applications. In a traditional pneumatic circuit, a three-position five-way valve is used to control the air inlet and exhaust with a single pressure, which has low efficiency. This paper proposed a novel bridge-type circuit with variable pressure control using four on-off valves to improve the energy efficiency of compressed air for pneumatic actuators. The key idea of the method was to use air expansion energy to do work. Reducing the volume of consumed air was the goal, and a numerical method was presented to calculate the optimal on-off time sequence of the four valves using nonlinear dynamic optimization. The sequence was obtained based on the combination of a finite element polynomial configuration method and a reduced space sequential quadratic programming algorithm. Then, experimental validation was conducted to illustrate the energy efficiency, including pneumatic cylinder motion test under different conditions. Compared with the traditional circuit, the experimental results show that the bridge-type circuit put forward by this paper can significantly improve the energy efficiency of pneumatic driving systems by 50–70%. Additionally, the bridge-type circuit allows the piston to move smoothly to the end of the stroke, which can take the place of the function of cushion component and speed control valve of the traditional circuit. Highlights: A novel bridge-type circuit with variable pressure control is used to improve the energy efficiency. The optimal on-off time sequence of the four valves are calculated using nonlinear dynamic optimization. Compared with the traditional circuit, the bridge-type circuit can significantly improve the energy efficiency by 50–70%. The piston reached the end of the stroke much more smoothly, avoiding collision and crawling phenomenon.